Interventions To Improve Parent–Adolescent Communication On Sexual And Reproductive Health: A Scoping Review - Marilia Reis; Andari Wuri Astuti; Dewi Rokhanawati (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Adolescence is a transitional period marked by significant physiological, psychological, and social changes. During this stage, adolescents are vulnerable to sexual and reproductive health (SRH) problems, including teenage pregnancy and sexually transmitted infections (STIs). Parents play a crucial role as primary sources of SRH information for adolescents; however, communication regarding SRH is often influenced by socio-cultural norms, stigma, and limited parental knowledge. Method: This scoping review aimed to identify interventions that improve parent–adolescent communication on sexual and reproductive health. Literature searches were conducted in PubMed, ScienceDirect, and Wiley Online Library databases for articles published between 2015 and 2025. The screening process followed predefined eligibility criteria, including studies discussing parent–adolescent communication on SRH, adolescent health programs, or sex education policies. Only full-text articles published in English or Indonesian were included. Study quality was appraised using the Joanna Briggs Institute (JBI) critical appraisal tool. A total of 10 studies met the inclusion criteria and were analyzed. Data were extracted using a charting table including author, year, country, study design, participants, data collection methods, and key findings Result: The review identified several effective interventions for improving parent–adolescent SRH communication, including digital-based interventions, youth-friendly health services, school-based programs, maternal empowerment initiatives, and formal or non-formal SRH education programs. These interventions improved parental knowledge, communication skills, and adolescent access to accurate SRH information. In addition, the interventions contributed to reducing barriers such as socio-cultural stigma, religious norms, gender-related issues, fear, limited parental education, and the perception that sexuality is a taboo topic. Conclusion: Interventions involving families, schools, healthcare services, and community-based educational approaches are effective in strengthening parent–adolescent communication regarding sexual and reproductive health. These strategies may contribute to improving adolescent SRH outcomes and reducing socio-cultural barriers that hinder open communication about sexuality